2010
DOI: 10.1002/gcc.20842
|View full text |Cite
|
Sign up to set email alerts
|

Intensity‐dependent constitutional MLH1 promoter methylation leads to early onset of colorectal cancer by affecting both alleles

Abstract: Constitutional epimutation is one of the causes for MLH1 gene inactivation associated with hereditary non-polyposis colon cancer (HNPCC) syndrome. Here we investigate MLH1 promoter hypermethylation in 110 sporadic early-onset colorectal cancer patients. Variable levels of hypermethylation were detected in 55 patients (50%). Importantly a reduced MLH1 gene expression was found in patients with high-level methylation, with the association of microsatellite instability (MSI) in their tumor cells. Such high-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 16 publications
1
29
0
2
Order By: Relevance
“…8 Approximately 40 index cases of constitutional MLH1 methylation have been reported. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, the prevalence of MLH1 constitutional epimutations is still unknown. Most studies addressing this issue have enriched their sampling with patients affected with CRC showing loss of MLH1 protein expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Approximately 40 index cases of constitutional MLH1 methylation have been reported. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, the prevalence of MLH1 constitutional epimutations is still unknown. Most studies addressing this issue have enriched their sampling with patients affected with CRC showing loss of MLH1 protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…13,17,20,22 In other cases, series were enriched for patients with CRC at an age of onset below 50 years. 9,14,17,23 In a very few cases genetic alterations in cis (gross rearrangements and variants in the promoter region) have been identified as responsible for the methylation. 13,16,19 In these cases, an autosomal dominant pattern is readily observed.…”
Section: Introductionmentioning
confidence: 99%
“…76 We have many references on such phenomena in extracutaneous pathology. For instance, MLH1 promoter hypermethylation has been related to cancers of the ovary, 82 colon, 83 esophagus, 84 and stomach. 85 The epigenetic inactivation of MLH1 is related to approximately 12% of all colonic cancers.…”
Section: Studies On Somatic Mutationsmentioning
confidence: 99%
“…In LS patients, lifetime risk for CRC may be 60-80%, and age at diagnosis is typically 15-20 years younger than in sporadic cases. However, recent studies have suggested that the average age at diagnosis in a certain proportion of LS patients may be close to that of sporadic cases [2,3,13,[16][17][18][19]. If familial CRC is suspected, it is recommended to start surveillance every 3-5th year from 40 years of age, or from 10 years before the youngest afflicted individual was diagnosed in the family.…”
Section: Introductionmentioning
confidence: 98%